The potential role of nuclear energy in mitigating CO2 emissions in the United Arab Emirates - Jamil AlFarra, Hasan (2011)
The annual CO2 emissions have more than doubled in the UAE since 1990. Electricity generated by fossil fuels is responsible for almost half of the country's emissions. Keeping with the Kyoto Protocol, the UAE decided to integrate nuclear energy into the electricity scheme to mitigate CO2 emissions as declared by the government (Embassy-of-UAE, 2009, ENEC, 2010b). This paper evaluates the effectiveness of the UAE's proposed nuclear energy strategy in mitigating CO2 emissions from the built environment up to year 2050. The IAEA's simulation model “MESSAGE” is used to estimate the energy demand and CO2 emissions in the UAE up to year 2050. Several energy supply/fuels scenarios are modeled and simulated including the following: Business as Usual (BaU), the UAE proposed nuclear strategy (APR1400) as well as 12 more aggressive Clean Energy Era (CEE) proposed scenarios. Nuclear energy, especially in its extreme CEE scenario (8NPPs), was found to be more practical option in mitigating CO2 than renewable energy and carbon capture and sequestration among the simulated scenarios. Nuclear energy also demonstrated an economic viability. The cost of electricity produced from nuclear energy was calculated to be 3.2 cents/kWh, significantly less than the current cost of 8.15 cents/kWh for electricity generation from fossil fuels in the UAE.